GAMBARAN SEL DARAH PUTIH DAN OVARIUM DOMBA DENGAN PEMBERIAN KULIT PISANG SEBAGAI PENGGANTI KONSENTRAT KOMERSIL - , FANDY YUDHISTIRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Banana peel is one of the waste which can be a potential alternative animal feed to become substitute commercial concentrate for sheeps in Indonesia. Banana peel contains protein, carbohydrate, mineral, antioxidant and phytoestrogen. The purpose of this research is to analyze the effect of feeding banana peel towards white blood cell profile and ovary size of sheep. The research was conducted at the sheep pens belong to Mr.Sadiyan, who addressed at Blendung RT 01/ RW 21, Sumbersari, Moyudan, Sleman. The method was using treatment for 4 weeks with 12 local female sheeps 8 months until 1 years old divided into four groups, each group consist of 3 sheeps. Control group (K) being fed with forage and the mixture of bran pollard and bran. Treatment 1 group (P1) being fed with forage and the mixture of 90% bran and 10% banana peel concentrate. Treatment 2 group (P2) being fed with forage and the mixture of 70% bran and 30% banana peel concentrate. Treatment 3 group (P3) being fed with forage and the mixture of 50% bran and 50% b anana peel concentrate. Feeding banana peel concentrate have been done every 2 days for 3 weeks. Blood sampling was collected on week 1 and 4 used 3 cc syringe and eppendorf tube with EDTA through jugularis vein. Ovarium size was determined with ultrasonography on week-4. White blood cell profile and ovarium was analyzed statistically with ANOVA test. The results showed that the total number of leukocytes sequentially from the week-1 are P1, P2, P3,K 10167 ± 2059, 12333 ± 1944, 10667 ± 4517, 10550 ± 4157. The week-4 are 9950 ± 705, 9533 ± 4171, 9267 ± 2287, 7567 ± 2458. The percentage of neutrophils week-1 sequentially are 58 ± 7, 50 ± 12, 54 ± 15, 48 ± 9. The week-4 are 63 ± 8, 37 ± 4, 48 ± 13, 49 ± 28. The percentage of eosinophils week-1 sequentially are 7 ± 8, 15 ± 5, 11 ± 6, 14 ± 6. The week-4 are 7 ± 3, 23 ± 12, 17 ± 17, 25 ± 13. The percentage of lymphocytes week-1 sequentially are 30 ± 2, 30 ± 10, 37 ± 15, 37 ± 12. The week-4 are 29 ± 9, 39 ± 15, 35 ± 11, 27 ± 21. The ovarium size sequentially from P1, P2, P3, K are 1,27 ± 0,06, 1,27 ± 0.6, 1,30 ± 0,10, 1,37 ± 0,15. ANOVA analysis results on week 1 and week 4, there were no difference (P>0,05) between the control and treatment comparisons. It has been proven that feeding banana peel was able to substitued bran concentrate as an alternative commercial concentrate.